2016
DOI: 10.1021/acsami.6b09581
|View full text |Cite
|
Sign up to set email alerts
|

Thermally-Induced Triple-Shape Hydrogels: Soft Materials Enabling Complex Movements

Abstract: Shape-memory hydrogels enable directed movements of a specimen in response to temperature, whereby crystallizable switching segments incorporated as side chains resulted in constant degrees of swelling during the shape-memory cycle. Here we report about hydrogels exhibiting a thermally induced triple-shape effect that allows complex movements of soft materials with two almost independent shape changes. Potential applications for those soft triple-shape materials are two-step self-unfolding devices or temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…During the programming procedure of changing the temperature, two distinct temporary shapes can be memorized and recovered through crystallization and amorphization of hydrophobic side chains. 42 2.2.2 Different stimuli-triggered triple-/multi-shape memory effects. As different stimuli can be introduced step by step, combining non-interfering interactions in one material provides an efficient way to create triple-/multi-shape memory materials.…”
Section: Triple-/multi-shape Memory Hydrogelsmentioning
confidence: 99%
“…During the programming procedure of changing the temperature, two distinct temporary shapes can be memorized and recovered through crystallization and amorphization of hydrophobic side chains. 42 2.2.2 Different stimuli-triggered triple-/multi-shape memory effects. As different stimuli can be introduced step by step, combining non-interfering interactions in one material provides an efficient way to create triple-/multi-shape memory materials.…”
Section: Triple-/multi-shape Memory Hydrogelsmentioning
confidence: 99%
“…For the shape memory hydrogels, the special circumstance is that the plenty of water inside promotes the motion of polymer chains and weakens the fixation for the temporary shape. The temporary shape is recovered to the original (permanent) shape induced by some external stimuli, which promises the shape memory hydrogels potential applications in soft actuators, such as smart valves for flow control, sequential “blooming” of artificial flowers, and cell encapsulating and detaching. [3d,e] However, all of these actuations are one‐off and the original shape cannot convert to the temporary shape spontaneously and reversibly .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, shape memory hydrogels have been investigated in recent years. Lendlein et al have reported a shape memory hydrogel actuated by temperature change through crystallization and amorphization of hydrophobic side chains [30]. Chen et al have fabricated a double layer self-deformed shape memory hydrogel which includes a thermo-responsive actuating layer and a pH-responsive memorizing layer [31].…”
Section: Introductionmentioning
confidence: 99%